COVID-19 Vaccination and Acute Anterior Uveitis—A Case Control Study - Asaf Shemer; Amit Toledano; Aya Altarescu; Biana Dubinsky-Pertzov; Assaf Rozenberg; Idan Hecht; Adi Einan-Lifshitz; Eran Pras (Vaccines)
Objective: To evaluate the association between the BNT162b2 (Pfizer-BioNTech®) coronavirus disease vaccine and new-onset anterior uveitis. Methods: A retrospective case control study of patients admitted and diagnosed with new-onset acute anterior uveitis, and matched controls admitted for other reasons (1:3 ratio), was completed. Rates of exposure to the BNT162b2 vaccine were compared between groups, and odds ratios for exposure to the vaccine were calculated. A secondary analysis of the overall number of patients with new-onset anterior uveitis in the six preceding years was conducted. This study was conducted in one academic center in Israel. Results: A total of 16 patients were admitted for acute anterior uveitis during the study period. Of the 16 cases, 11 (69%) received the first dose of the BNT162b2 vaccine prior to presentation and 8 (50%) also received the second dose. This compares to 39 (81.2%) in the control group. The odds ratio for exposure to the vaccine among cases was 0.508 (95% confidence interval 0.141–1.829, p = 0.300). Compared with preceding years, the rate of cases diagnosed with acute anterior uveitis in 2021 was similar to the six preceding years (mean 11.8 ± 3.4 cases). Conclusions: In this case control study and comparison with preceding years, we found no evidence to suggest an association between vaccination with the BNT162b2 (Pfizer-BioNTech®) COVID-19 vaccine and new-onset acute anterior uveitis.